CHEMICAL MEASURES FOR CONTROLLING PESTS IN INTENSIVE PISTACHIO ORCHARDS (Multidisciplinary Journal of Science and Technology, 2025)
This article provides an overview of the distribution and harmful effects of sucking pests in intensive pistachio orchards. Particular attention is given to their bioecological characteristics and the damage they cause to plant growth and yield. Furthermore, the article discusses control strategies with a focus on the application of chemical methods. The biological effectiveness of insectoacaricides against the dominant pest species has been evaluated, providing a scientific basis for improving integrated pest management (IPM) programs in intensive pistachio cultivation.